Nosocomial, Healthcare-Associated, and Community-Acquired Acinetobacter baumannii in China: Clinical Characteristics, Antimicrobial Resistance Patterns and Risk Factors Associated with Carbapenem Resistance - Li Y; Zhang J; Gu Y; Wang L; Hu J (Infection and Drug Resistance, 2024)
Yuqing Li,1,* Jiachen Zhang,2,* Yingjuan Gu,1 Ling Wang,1 Jing Hu1 1Department of Nosocomial Infection Administration, Zhujiang Hospital, Southern Medical University, Guangzhou, People’s Republic of China; 2Clinical Research Center, Nanfang Hospital, Southern Medical University, Guangzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jing Hu, Department of Nosocomial Infection Administration, Zhujiang Hospital, Southern Medical University, Guangzhou, Guangdong, 510282, People’s Republic of China, Tel +8620-61643605 ; +8615622316318, Email hjalzh@smu.edu.cnBackground: Acinetobacter baumannii (A. baumannii) is an widespread pathogen and carbapenem-resistant strains are great threat to hospitalized patients. This study is aimed to investigate the clinical characteristics, antimicrobial resistance patterns, and risk factors associated with carbapenem resistance in nosocomial, healthcare-associated (HCA), and community-acquired (CA) A. baumannii infections.Methods: This study retrospectively reviewed cases in a tertiary hospital in southern China between January 1, 2019, and December 31, 2021. Univariate and multivariate logistic regression analyses were performed to identified the risk factors of carbapenem resistance in nosocomial, HCA and CA A. baumannii infections.Results: A total of 391 patients with A. baumannii infection were included. Of these patients, 96 (24.6%) had nosocomial infections, 215 (55.0%) had HCA infections, and 80 (20.5%) had CA infections. The overall 30-day mortality rates of nosocomial and HCA infection patients was significantly higher than that of CA infection (P< 0.05). The incidence of antimicrobial resistance was also higher in nosocomial and HCA bacteremia than that in CA bacteremia (P< 0.05). Logistic regression analysis identified age ≥ 60 years, urethral catheterization, and exposure to two or more antibiotics as the independent risk factors for carbapenem-resistant A. baumannii (CRAB) infection in the nosocomial infection group and exposure to two or more antibiotics and endotracheal intubation in the HCA infection group. However, malignant tumors and hematological diseases were identified as protective factors against CRAB infection in the HCA group.Conclusion: These data suggest that HCA A. baumannii infection is quite different from CA infection, with antimicrobial resistance and 30-day mortality rates similar to those of nosocomial infections. Additionally, the risk factors for CRAB development in the CA, HCA, and nosocomial groups were not the same, which may provides the help for controlling practices and instruction empirical clinical medication.Keywords: Acinetobacter baumannii, community-acquired, healthcare-associated, nosocomial, antimicrobial resistance, risk factor